Department of mining Engineering, Shahrood Branch, Islamic Azad University, Shahrood, Iran - MOLAYI, MOHAMAD IMAN; Rad, Navid Fatehi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to investigate the role of Resalat Social Development Network in improving small and home businesses in Golbaf District. In terms of purpose, this research was applied research, while it employed a descriptive correlational design as research method. The statistical population of this study included all members of Resalat Social Assistance Center in Golbaf who have used the entrepreneurial facilities of this center (n=233), 145 of which were randomly selected as the sample population using Krejcie-Morgan table and stratified sampling method. For data collection, two inventories of home business questionnaire with a validity of 0.87 and the questionnaire for the development of Resalat social network with a validity of 0.89 were employed. Descriptive statistics (provided in statistical table and chart) and Student’s t-distributions were used to analyze the data. The results indicate the overall impact of Resalat Social Development Network on small and home businesses. Furthermore, the impact of Resalat Social Development Network on all components of home business (livestock and clothing) was also confirmed. According to the research findings, it can be concluded that the activity and expansion of entrepreneurial social networks greatly contributes to small and home businesses.